(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Abdulasis Yassin Abbaskhilmi (University Diyala, Diyala, Iraq) In the process of professional theater formation in Iraq the choice of translated plays for the stage was of a great importance. A.P.Chekhov became one of the most favorite Russian playwrights in the Arab countries. During the previous century practically all Chekhov’s plays were staged by Iraqi theatre parties. Salakh Alkasab, the creator of Iraqi experimental “theatre of visual perception”, also staged his plays. This type of theatre in general is based not upon dialogues, but upon spectacular and peculiar performances, distribution of author’s and director’s ideas between artificially created characters. Here the thing, which is called Chekhov’s “underlying theme” by Russian scientists, is bared and put on the stage. It resulted in a great difference between Chekhov’s text and the text of the performance. The director put away characters, substitutes cues for actions. In the play “The seagull” S.Alkhasab concentrated on the love-line Treplev – Nina and on the confrontation between Treplevinnovator and his mother. In the play “Uncle Vanya” characters are placed not in the space of the manor, but in the ward. In “Three sisters” artistic space has become dominating category in the play. The director uses symbolic language, for instance, he puts Destiny on the stage. At the heart of performance there is tendency to show Chekhov’s innovations. Iraqi critics have ambiguous thoughts about S.Alkhasab’s performances. Key words: Chekhov, plays, Alkhasab, experimental theory, Iraq. DOI 10.23683/1995-0640-2019-1-28-35